Liposomes as Multifunctional Nano-Carriers for Medicinal Natural Products - Cheng, Xiamin; Yan, Hui; Pang, Songhao; Ya, Mingjun; Qiu, Feng; Qin, Pinzhu; Zeng, Chao; Lu, Yongna (Frontiers in Chemistry, 2022)
Although medicinal natural products and their derivatives have shown promising effects in disease therapies, they usually suffer the drawbacks in low solubility and stability in the physiological environment, low delivery efficiency, side effects due to multi-targeting and low site-specific distribution in the lesion. In this review, targeted delivery was well-guided by liposomal formulation in the aspects of preparation of functional liposomes, liposomal medicinal natural products, combined therapies and image-guided therapy. This review is believed to provide a useful guidance to enhance the targeted therapy of medicinal natural products and their derivatives.